Isolation and Identification of Soil Bacteria in Pracimaloyo Public Cemetery, Kartasura - Adityaradja, Bagas; Tyastuti, Erma Musbita; Sidiq, Yasir; Rahayu, Triastuti (Universitas Muhammadiyah Surakarta, 2023)
In The Pracimaloyo Public Cemetery, the body’s decomposition occurs continuously, producing soil nutrients and minerals that affect the growth of bacteria. Bacterial population data from the cemetery area is still very limited, whereas cemeteries hold the risk of contamination with pathogenic bacteria. This research aims to find out how the population and diversity of bacteria in the Pracimaloyo Public Cemetery. Soil samples were taken from the Pracimaloyo cemetery at 2 locations (blocks 8 and 18), each at 20 and 50 cm depth. Soil samples are inoculated in Nutrient Agar media using the spread plate method. After 48 hours, colony counting, colony morphology, and gram staining observations were carried out. The rate of soil bacterial populations in blocks 8 and 18 at a depth of 20 cm was 4.23 × 107 CFU/g and 9.79 × 107 CFU/g, while at depths of 50 cm, it was 1.94 × 107 CFU/g and 1.92 × 107 CFU/g. The morphology of the bacterial colonies is dominated by circular shape, entire margin, flat elevation, and white color. 20 isolates are gram-negative and 16 isolates are gram-positive, the cell form is dominated by the bacillus.